Study on the protective effects and mechanisms of eleutherococcus senticosus on korsakoff syndrome - Jiang, Shan; Wang, Yaoai; Ren, Yifan; Sun, Xiaoran; Ding, Jiaxin; Lou, Siju; Bai, Xueke; Hai, Xin; Ramenskaya, Galina; Zhang, Ning (Frontiers in Neuroscience, 2025)
Korsakoff syndrome (KS), as a central nervous system disorder caused by prolonged alcohol exposure, is primarily characterized by cognitive dysfunction, which has long-term effects on patients’ lives, and there is currently a lack of effective therapeutic drugs. Eleutherococcus senticosus (ES), as a traditional medicinal plant, has significant antioxidant, anti-inflammatory, and central nervous system protective effects, and is widely used as ethnopharmacological agen. This article elaborates on the main pathogenesis and the latest research progress of KS, summarizes the mechanisms of central nervous system protection by ES and its active components, and explores its main mechanisms and targets for treating KS, aiming to provide drug options for the effective treatment of KS while promoting the development and utilization of the medicinal value of ES.